Lessons from the submission and approval process of energy-efficiency CDM baseline and monitoring methodologies - Felicia Müller-Pelzer; Axel Michaelowa (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2005)
Energy efficiency is a CDM project type that suffers from high methodology rejection rates. 43 baseline and monitoring methodologies for CDM energy efficiency projects are analyzed with respect to reasons for approval / rejection by the CDM Executive Board. Most methodologies have been rejected because they did not comply with implicit quality standards regarding presentation and conservativeness. Also, tools to select the baseline scenario and to prove additionality were frequently lacking. If the level or the quality of production in the baseline or the project scenario changes, a simple before-after-comparison is not valid. Black box models are not accepted and methodologies should be sufficiently differentiated to account for specific (technical) circumstances. The remaining lifetime of equipment has to be taken into account. Often, elements of small-scale methodologies have been retained in approvals of large-scale methodologies.
Keywords: 330